Menganalisis Kemampuan Siswa Sekolah Dasar dalam Menulis Sebuah Karangan Teks Deskriptif - Atastasial, Mawarni; Agustii, Rieke Diah; Chandra, Chandra; Wijanarko, Tiok (Lembaga Yasin AlSys, 2024)
This study aims to assess the ability of elementary school students to write descriptive texts. The research focuses on explanatory descriptive text composition. A qualitative research approach was employed for this study. The subjects supporting this research are elementary school students. Consequently, students are expected to develop writing skills through the practice of composing descriptive texts. Through this writing activity, students are also anticipated to cultivate a positive attitude. The researcher evaluates the students' abilities not only based on their final output but also on their process in creating the texts.